In vivo ultrasonic detection of polyurea crosslinked silica aerogel implants. - Firouzeh Sabri; Merry E Sebelik; Ryan Meacham; John D Boughter; Mitchell J Challis; Nicholas Leventis (PLoS ONE, 2013)
BACKGROUND: Polyurea crosslinked silica aerogels are highly porous, lightweight, and mechanically strong materials with great potential for in vivo applications. Recent in vivo and in vitro studies have demonstrated the biocompatibility of this type of aerogel. The highly porous nature of aerogels allows for exceptional thermal, electric, and acoustic insulating capabilities that can be taken advantage of for non-invasive external imaging techniques. Sound-based detection of implants is a low cost, non-invasive, portable, and rapid technique that is routinely used and readily available in major clinics and hospitals. METHODOLOGY: In this study the first in vivo ultrasound response of polyurea crosslinked silica aerogel implants was investigated by means of a GE Medical Systems LogiQe diagnostic ultrasound machine with a linear array probe. Aerogel samples were inserted subcutaneously and sub-muscularly in a) fresh animal model and b) cadaveric human model for analysis. For comparison, samples of polydimethylsiloxane (PDMS) were also imaged under similar conditions as the aerogel samples. CONCLUSION/SIGNIFICANCE: Polyurea crosslinked silica aerogel (X-Si aerogel) implants were easily identified when inserted in either of the regions in both fresh animal model and cadaveric model. The implant dimensions inferred from the images matched the actual size of the implants and no apparent damage was sustained by the X-Si aerogel implants as a result of the ultrasonic imaging process. The aerogel implants demonstrated hyperechoic behavior and significant posterior shadowing. Results obtained were compared with images acquired from the PDMS implants inserted at the same location.